Organotypic Cultures as a Model of Parkinson´s Disease. A Twist to an Old Model - Katja Stahl; øivind Skare; Reidun Torp (The Scientific World Journal)
Organotypic cultures from the ventral mesencephalon (VM) are widely used to model Parkinson's disease (PD). In this method, neurotoxic compounds have traditionally been applied to the media to induce a uniform dopaminergic (DAergic) cell death in the tissue slices, regardless of the variation existing among slices. This study demonstrates a refinement of the toxic induction technique. We show that unilateral application of 6-hydroxydopamine (6-OHDA) at the tissue surface by means of a microelectrode causes a precisely localized cell death that closely resembles an in vivo stereotactic model. This technique introduces an internal control that accounts for variation between slices and enables a precise quantification of the cell loss due to the toxin in use. We characterized organotypic VM cultures in terms of effects of 6-OHDA toxicity and number of DAergic neurons as judged by immunofluorescence and Western blots. Our findings illustrate that this new application technique greatly improves the representativeness of organotypic cultures as a model for PD.We characterized organotypic VM cultures in terms of effects of 6-OHDA toxicity and number of DAergic neurons as judged by immunofluorescence and Western blots. Our findings illustrate that this new application technique greatly improves the representativeness of organotypic cultures as a model for PD.